Network pharmacology-based approach to explore the underlying mechanism of sinomenine on sepsis-induced myocardial injury in rats - Sun, Linggang; Chen, Zhiyun; Ni, Yunjie; He, Zhengfei (Frontiers in Pharmacology, 2023)
Background: Sepsis, a systemic disease, usually induces myocardial injury (MI), and sepsis-induced MI has become a significant contributor to sepsis-related deaths in the intensive care unit. The objective of this study is to investigate the role of sinomenine (SIN) on sepsis-induced MI and clarify the underlying mechanism based on the techniques of network pharmacology. Methods: Cecum ligation and puncture (CLP) was adopted to induce sepsis in male Sprague-Dawley (SD) rats. Serum indicators, echocardiographic cardiac parameters, and hematoxylin and eosin (H&E) staining were conducted to gauge the severity of cardiac damage. The candidate targets and potential mechanism of SIN against sepsis-induced MI were analyzed via network pharmacology. Enzyme-linked immunosorbent assay was performed for detecting the serum concentration of inflammatory cytokines. Western blot was applied for evaluating the levels of protein expression. Terminal deoxynucleotidyl transferase-mediated dUTP biotin nick end labeling assay was applied to assess cardiomyocyte apoptosis. Results: SIN significantly improved the cardiac functions, and attenuated myocardial structural damage of rats as compared with the CLP group. In total, 178 targets of SIN and 945 sepsis-related genes were identified, and 33 overlapped targets were considered as candidate targets of SIN against sepsis. Enrichment analysis results demonstrated that these putative targets were significantly associated with the Interleukin 17 (IL-17) signal pathway, inflammatory response, cytokines-mediated signal pathway, and Janus Kinase-Signal Transducers and Activators of Transcription (JAK-STAT) pathway. Molecular docking suggested that SIN had favorable binding affinities with Mitogen-Activated Protein Kinase 8 (MAPK8), Janus Kinase 1 (JAK1), Janus Kinase 2 (JAK2), Signal Transducer and Activator of Transcription 3 (STAT3), and nuclear factor kappa-B (NF-κB). SIN significantly reduced the serum concentration of Tumor Necrosis Factor-α (TNF-α), Interleukin 1 Beta (IL-1β), Interleukin 6 (IL-6), Interferon gamma (IFN-γ), and C-X-C Motif Chemokine Ligand 8 (CXCL8), lowered the protein expression of phosphorylated c-Jun N-terminal kinase 1 (JNK1), JAK1, JAK2, STAT3, NF-κB, and decreased the proportion of cleaved-caspase3/caspase3. In addition, SIN also significantly inhibited the apoptosis of cardiomyocytes as compared with the CLP group. Conclusion: Based on network pharmacology analysis and corresponding experiments, it was concluded that SIN could mediate related targets and pathways to protect against sepsis-induced MI.